Asia and the world economy in historical perspective - Ronald Findlay (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper studies the political and economic evolution of trade and international relations of the nations and regions of Asia between themselves and the rest of the world over the past millennium, paying particular attention to: the Pax Mongolica and overland trade during the Middle Ages; the European intrusion at the turn of the fifteenth century and the impact of the New World; the spread of European imperialism and the rise of nationalism and the achievement of independence. A final section discusses the comparative evolution of Europe and Asia and the question of why the Industrial Revolution did not first occur in Asia.
Keywords: F54; F63; N10; N15; 330; Malthus-Ricardo model; dynastic cycle; globalization; catchup